Behaviour and analysis of concrete-filled rectangular hollow sections subject to blast loading. (August 2018) - Ritchie, Cameron B.; Packer, Jeffrey A.; Seica, Michael V.; Zhao, Xiao-Ling
Abstract: Concrete-filled Rectangular Hollow Sections have been tested under large-scale, far-field, air-blast loading for the first time. The concrete-filled, cold-formed steel tubes performed well under the blast loads, with a significant reduction in the global and local displacements compared to unfilled RHS members. The heavily instrumented tests provided a large quantity of response data that was used for the validation of numerical models. Numerical models of the concrete-filled steel tubes were first developed using explicit finite element methodologies. A parametric study was conducted with the validated finite element model to further characterize the response of the concrete-filled steel tubes under air-blast loading. The influence of several key variables on the response of the tubular members was determined and preliminary design guidance is provided. Finally, the test and finite element results were used to develop an idealized single-degree-of-freedom numerical model that is well-suited to future use in design problems. Highlights: Concrete-filled rectangular hollow sections tested by far-field blast loads for first time Concrete-filled members performed well, and better than unfilled members. Explicit finite element models developed and used for a subsequent parametric study Influence of key parameters was assessed and preliminary design aids are given. Single-degree-of-freedom model developed for future use in design problems.